Etične dileme v rehabilitaciji oseb po amputaciji uda - Burger, Helena (Rehabilitacija (Ljubljana), 2017)
The article presents the most frequent ethical dilemmas in rehabilitation of persons after amputation of lower or upper limb (from amputation to reintegration), and suggests some solutions.
Keywords: amputacija; Amputation; artificial limbs; ethical issues; Ethics; etične dileme; proteze; rehabilitacija; rehabilitation; vocational rehabilitation